Implementation of Character Based Learning Quality Improvement With Islamic Full Day School System in The Era of Industrial Revolution 4.0. - Mutohar, Prim Masrokan; Trisnantari, Hikmah Eva (Khatulistiwa, 2020)
This study aims to describe the implementation of improving character-based learning quality with the full day school system in the era of industrial revolution 4.0 held in elementary schools. Elementary School, as the foundation for education at the next level, must be in good condition, quality, and teach character values. Primary school is the foundation to be able to continue at the next school level. If the foundation is good and quality, students will find it easier to get succeed in carrying out learning in the next school. Quality learning is the key to the success of schools in creating effective schools, high quality, and demanded by the community. This study used a qualitative research approach with a multi-site study design at Al-Gontori Islamic elementary school and Al-Azhar Islamic Primary with a full day school system. The results of the study indicate that learning is carried out by using government curriculum integration with the school curriculum sourced from the teachings of Islam. Active learning is carried out in shaping the knowledge and skills needed by students in the industrial revolution era 4.0, planting morality, implementing character values that are the core values of the school, and forming Islamic culture. This is done so that students have personal and social skills in preparing quality human resources in the future. Learning quality is improved continuously so that students have the competence and character that are by the quality standards set by the school. The full-day school system can familiarize students in applying character values under the guidance and supervision of teachers.